The Effect of Muslim CEO, Women on Board and Profitability on Corporate Social Responsibility Disclosure - Silviani, Amanda Agnes; Nasrizal; Wiguna, Meilda; Indrawati, Novita (Future Science, 2023)
Corporate Social Responsibility (CSR) disclosure has attracted considerable attention from practice and academia. Corporate Social Responsibility (CSR) is an obligation that needs to be considered by the company to the environment around the company that contributes to the welfare of the community. In addition to the factors of profits obtained by the company (profitability) and gender diversity on the board of directors that affect corporate social responsibility. Islamic principles have actually taught business ethics that are seen as closely related to Corporate Social Responsibility (CSR), namely humans as caliphs (khalifah) and an approach consisting of three relationships (ukhuwwah), namely with the lord, with humans and with the environment. Thus, the purpose of this study is to determine the influence of Muslim CEO, women on board, and profitability on corporate social responsibility disclosure. The population in this study are banking companies listed on the Indonesia stock exchange for the period 2016-2019. The sampling technique in this study used purposive sampling techniques and obtained samples of 20 companies, so the amount of data processed was 80 companies. The data analysis used was multiple linear regression using SPSS version 25. The findings of this study show that Muslim CEO (? = 0.009) and women on board (? = 0.020) have an influence on corporate social responsibility disclosure, while profitability (? = 0.072) does not influence corporate social responsibility disclosure. Because of the fact, companies will focus more on allocating profits for investment or business continuity rather than spending costs on corporate social responsibility. We suggest that the profits earned by the company can be used for CSR disclosure programs, not just to reinvest capital for product development and company sustainability.